Factors Affecting Nepalese Youth Migration to Foreign Countries - Shah, Tejashwini; Dahal, Gangadhar (Nepalese Journal of Finance, 2025)
This study examines the factors affecting Nepalese youth migration to foreign countries. Brain drain is the dependent variable. The selected independent variables are employment, education, earning, skills and stability. The primary sources of data is used to assess the opinions of respondents regarding employment, education, earning, skills, stability and brain drain. The study is based on the primary data of 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of factors affecting Nepalese youth migration to foreign countries. The study showed a positive impact of employment on brain drain. It indicates that higher employment opportunities in abroad, higher would be the level of brain drain. Similarly, the study showed a positive impact of education on brain drain. It indicates that increase in prompt education facilities leads to increase in brain drain. Likewise, the study showed a positive impact of earning on brain drain. It indicates that higher earning capacity in abroad, higher would be the level of brain drain. Further, the study also showed a positive impact of skills on brain drain. It indicates that positive perception of youths on skills enhancement leads to increase in level of brain drain. In contrast, the study showed a negative impact of stability on brain drain. It indicates that political stability in nation leads to decrease in the level of brain drain.